Tuberculosis of the central nervous system - Mondol, BA; Siddiqui, MR; Mohammad, QD; Saha, NC; Hoque, MA; Uddin, MJ (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):312-22. The abstract of this article is available on the PubMed website